Filter-Feeding Bivalve Weakens Food Competition Between Crustaceans (Portunus trituberculatus, Marsupenaeus japonicus) in Integrated Culture Ponds: Evidence From 18S rDNA Barcoding and Stable Isotope Analysis - Xu, Xian; Dong, Shipeng; Zhang, Dongxu; Yu, Liye; Pu, Weijia; Xie, Yicheng; Shan, Hongwei; Wang, Fang (Frontiers in Marine Science, 2022)
In order to investigate the effects of razor clams (Sinonovacula constricta) on the food composition and isotopic niches of swimming crabs (Portunus trituberculatus) and kuruma shrimp (Marsupenaeus japonicus) in polyculture systems, this study analyzed 60 P. trituberculatus, 60 M. japonicus and 30 S. constricta to quantify the food sources, food source contributions, and isotopic niches of cultured organisms using 18S rDNA barcoding and stable isotope techniques. The results were as follows: (1) In the P. trituberculatus-M. japonicus (PM) polyculture system, the Sobs and Shannon-Wiener indices of the stomach contents of P. trituberculatus and M. japonicus were not significantly different (P > 0.05). In the P. trituberculatus-M. japonicus-S. constricta polyculture (PMS) system, the Sobs and Shannon-Wiener indices of the stomach contents of P. trituberculatus and M. japonicus were also not significantly different (P > 0.05), but the Sobs indices of P. trituberculatus in the PMS system were significantly higher than those in the PM system (P < 0.05), M. japonicus shows a similar pattern. (2) 18S rDNA barcoding analysis showed the dominant taxa in the stomach contents of both P. trituberculatus and M. japonicus in the PM system were Trebouxiophyceae, Embryophyta and Rotifera, and the food overlap between them was 0.8992, which was significant (Q > 0.6). In the PMS system, the dominant taxa in the stomach contents of P. trituberculatus were Chrysophyceae, Intramacronucleata, and Embryophyta, and in M. japonicus were Chrysophyceae, Embryophyta, and Bacillariophyceae, in this system the food overlap was 0.2061, which was not significant (Q < 0.6). (3) Stable isotope analysis suggested, in both systems, the main food sources of P. trituberculatus and M. japonicus were iced trash fish, zooplankton, phytoplankton, and organic particulate matter (POM). Iced trash fish accounted 77.67% of food sources for P. trituberculatus and 69.42% for M. japonicus in the PM system, and 60.82% and 57.60% in the PMS system. (4) The isotopic niche overlap between P. trituberculatus and M. japonicus was 5.69% in the PM system and 1.21% in the PMS system. These results suggested food competition between P. trituberculatus and M. japonicus, and S. constricta can reduce the competition and isotopic niche overlap, improve the contribution of food sources such as phytoplankton. Razor clams also serve to purify the water and improve the utilization of iced trash fish by filtering phytoplankton (51.10%), POM (32.25%), SOM (7.47%), and iced trash fish (9.18%). Thus, P. trituberculatus-M. japonicus-S. constricta is a healthy and sustainable culture model.